Family History as a Risk Factor for Peripheral Arterial Disease - Khaleghi, Mahyar; Isseh, Iyad N.; Bailey, Kent R.; Kullo, Iftikhar J. (The American journal of cardiology, 2014)
The association of a family history of peripheral arterial disease (PAD) with the presence of PAD is largely unknown. We conducted a case-control study of 2,296 patients with PAD (69 ± 10 years, 64% men) and 4,390 controls (66 ± 11 years, 62% men) identified from noninvasive vascular and stress testing laboratories at Mayo Clinic, Rochester, Minnesota, from October 2006 through June 2012. PAD was defined as an ankle brachial index of ≤0.9 at rest and/or after exercise, a history of lower extremity revascularization, or having poorly compressible leg arteries. Controls were patients with normal ankle brachial index or without a history of PAD. Family history of PAD was defined as having at least 1 first-degree relative who had undergone revascularization or stent placement for PAD before the age of 65 years. Logistic regression analyses were used to evaluate whether a family history of PAD was associated with the presence of PAD, independent of conventional risk factors. A family history of PAD was present more often in patients with PAD than in controls, with a resulting odds ratio (OR) of 2.20 (95% confidence interval [CI] 1.82 to 2.67). The association remained significant after adjustment for conventional risk factors (OR 1.97, 95% CI 1.60 to 2.42). The association was stronger in younger subjects (age <68 years; adjusted OR 2.46, 95% CI 1.79 to 3.38) than in older subjects (adjusted OR 1.61, 95% CI 1.22 to 2.12). A greater number of affected relatives with PAD was also associated with greater odds of presence of PAD (adjusted OR 1.86, 95% CI 1.48 to 2.33 and adjusted OR 2.56, 95% CI 1.60 to 4.11 for patients with 1 and ≥2 affected relatives with PAD, respectively). In conclusion, individuals with a family history of PAD have nearly double the odds of having PAD relative to those without such a history. •We conducted a large case-control study to investigate whether a family history of peripheral arterial disease (PAD) or coronary heart disease was associated with the presence of PAD.•We showed that a family history of PAD as well as of coronary heart disease were each independently associated with the presence of PAD, the former being more strongly associated.•In our study, parental or sibling history of PAD conferred similar odds.•We found that the association was age dependent, being stronger in younger individuals, and the magnitude of the association was greater in those with a greater number of affected relatives.